Deri sanayi atıksularının kimyasal koagülasyon ve elektrokoagülasyon ile arıtımı - Şanlı, Neslihan (Gebze Yüksek Teknoloji Enstitüsü, Lisansüstü Eğitim Enstitüsü, 2006)
ivÖZETTEZ BAŞLIĞI: Deri Sanayi Atıksularının Kimyasal Koagülasyon veElektrokoagülasyon İle ArıtımıYAZAR ADI : Neslihan ŞANLIBu çalışmada, deri sanayilerine ait olan merkezi Atıksu Arıtma Tesisinin önçöktürme atık suyunda farklı kimyasal koagülan maddeler kullanılarak kimyasalkoagülasyon (CC) ile arıtılabilirlik çalışmalarının yanında, ön çöktürme ve son çöktürmehavuz çıkış atıksuları elektrokimyasal metodlardan biri olan elektrokoagülasyon (EC) ilearıtılabilirliği araştırılmıştır.Bu amaçla kimyasal koagülasyon deneylerinde Al2(SO4)3.18H2O, AlCl3.6H2O, Fe2(SO4)3.7H2O ve FeCl3.6H2O tuzları koagulan olarak kullanılmıştır. Arıtım verimi üzerinekoagulan dozajı ve pH etkisi incelenmiştir. Bu deneylerde demir içeren koagülanmaddeler kullanıldığında daha etkili bir biçimde verimlerin arttığı gözlenmiştir.Atıksuyun kendi pH değerinde daha iyi sonuçlar elde edilmiştir.EC `da demir elektrodlar kullanılarak; COD, TS, TCr, NH3-N, AKM giderimiüzerine akım yoğunluğu ve zaman gibi parametrelerin etkisi araştırılmıştır.Elektrokoagülasyon uygulamaları sonunda ön çöktürme atıksuların da %60 AKM ve %30KOİ giderim verimi elde edilmiştir. Son çöktürme atıksuyun da ise %85 AKM ve %35KOİ giderim verimi elde edilmiştir. Her iki atıksudada %20'lerde amonyak azotu (NH3-N) giderimi elde edilmiş ancak, bu sonuçların yeterli görülmemesi sebebi ile NH3-Ngiderimi uygulaması için ayrı bir sistem üzerinde çalışmalar yapılmıştır.Son çöktürme havuzu çıkış atıksuları bir zeolit türü olan clinoptilolit kullanılarakfarklı zaman ve pH değerlerinde NH3-N giderimi araştırılmıştır. Atıksu pH = 7-9 ve 15dakikalık bir adsorpsiyon süresinde yaklaşık 16 mg NH3-N/g zeolit adsorpsiyonusağlanmış olup, son çöktürme atıksuyu NH3-N'nun %40'ı giderilmiştir.

vSUMMARYTITLE OF THE THESIS: Tanning Industrial Wastewater Treatment byChemical Coagulation and ElectrocoagulationAUTHOR: Neslihan ŞANLIThe Purpose of this study is to research the chemical coagulation on waste water ofprimary sedimentation basin which is belongs to Tanning Industry Waste WaterTreatment Plant by using various type chemical substances. Besides, electro coagulationprocess is applicated on waste water of primary sedimentation basin and finalsedimentation basin.For this purpose, during chemical coagulation experiments, Al2(SO4)3.18H2O,AlCl3.6H2O, Fe2 (SO4)3.7H2O and FeCl3.6H2O is used as coagulated materials. Thecoagulate dosage and pH range effects to the efficiency of treatment is researched.During these experiment more efficiency has observed when the coagulate materialswhich are including ferric salt were used. The best result were obtained when pH 7,5.An electrochemical reactor including monopolar (iron) electrodes in parallelconnections was designed. The effect of parameters such as pH, current density andoperating time on COD, TS, TCr, NH3-N and SS removal were investigated. At the endof experiments, efficiency of waste water treatment with energy consumption per cubicmeter is given. At the end of EC 30% COD and 60% SS disposal has obtained in theprimary sedimentation basin of waste water. In the same condition, 35% COD and 85%SS disposal has obtained in the final sedimentation basin of waste water. Disposal ofNH3-N has calculated 20% for both waste waters. However, due to the results were notquite satisfactory, for application of disposal of NH3-N another system improvement hasstarted.The efficiency of Ammonium Nitrogen treatment is researched with different timeand pH range by using zeolite (clinoptilolite) from waste water of final sedimentationbasin.
Tanning industrial wastewater treatment by chemical coagulation and electrocoagulation
Keywords: Çevre Mühendisliği; Environmental Engineering